PENGARUH EFEKTIVITAS ABSENSI DIGITAL MyDAMRI TERHADAP KEDISIPLINAN KARYAWAN DI PERUM DAMRI CABANG MAKASSAR - Nadria Misran; Andi Jam'an; Sitti Nurbaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of the effectiveness of MyDAMRI digital attendance on employee discipline at Perum DAMRI Makassar Branch. This research uses an explanatory quantitative approach with simple linear regression method. The population consists of 102 employees of Perum DAMRI Makassar Branch, with a sample of 82 respondents selected using random sampling technique based on the Slovin formula. Data were collected through questionnaires measured using a 5-point Likert scale and analyzed using SPSS software through validity tests, reliability tests, classical assumption tests, simple linear regression, and hypothesis testing. The results show that MyDAMRI digital attendance effectiveness has a positive and significant effect on employee discipline (coefficient = 0.873, t = 10.711, sig. = 0.001). The correlation coefficient (R = 0.768) indicates a strong relationship between the two variables, while the coefficient of determination (R² = 0.589) shows that 58.9% of the variation in employee discipline can be explained by digital attendance effectiveness. These findings confirm that a practical, efficient, transparent, and secure digital attendance system encourages employees to be more disciplined in adhering to work rules and regulations.